Ethics in a computing culture - Brinkman, Bo (Cengage Learning, 2013)
ETHICS IN A COMPUTING CULTURE introduces key ideas in moral theory and professionalism to explore the hottest topics in computer ethics. With a unique blend of theory, application, and critical thinking exercises, each chapter underscores the interdisciplinary links between computing and diverse areas of study. Abundant multicultural cases are presented throughout to highlight contrasts and conflicts in ethical perspectives across the globe. ETHICS IN A COMPUTING CULTURE encourages students to continually read, reflect and write to hone sharp critical thinking skills. Students learn that that computing is not a purely technical discipline but one with moral and social implications that affect everyday life.